2017
DOI: 10.3324/haematol.2015.139162
|View full text |Cite
|
Sign up to set email alerts
|

Results and conclusions of the European Intergroup EURO-LB02 trial in children and adolescents with lymphoblastic lymphoma

Abstract: In the European Intergroup EURO-LB02 trial, children and adolescents with lymphoblastic lymphoma underwent the non-Hodgkin lymphoma Berlin-Frankfurt-Münster protocol without prophylactic cranial radiotherapy. The primary aims of this trial were to test whether replacing prednisone with dexamethasone during induction increases event-free survival in the subgroups with T-cell lymphoblastic lymphoma and whether therapy duration could be reduced from 24 to 18 months (factorial design, randomizations). These questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 41 publications
8
95
2
4
Order By: Relevance
“…28 Fifty-eight patients (77%) were treated according to NHL-subtypedirected protocols (pediatric type, n 5 57; adult type, n 5 1; B-NHL-block therapy: B-NHLs, n 5 38, ALCL, n 5 14; leukemiatype therapy: LBL, n 5 4, PTCL, n 5 2), and 17 patients (23%) received miscellaneous therapies. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Thirty-one patients (41%) were treated with chemotherapy only, 15 (20%) were treated with chemotherapy 1 rituximab, 24 (32%) were treated with chemotherapy 1 radiotherapy, and 2 (3%) were treated with chemotherapy 1 rituximab 1 radiotherapy. One patient underwent observation alone after total resection, 1 received no therapy for 3 months for logistic reasons, and 1 patients remained without therapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…28 Fifty-eight patients (77%) were treated according to NHL-subtypedirected protocols (pediatric type, n 5 57; adult type, n 5 1; B-NHL-block therapy: B-NHLs, n 5 38, ALCL, n 5 14; leukemiatype therapy: LBL, n 5 4, PTCL, n 5 2), and 17 patients (23%) received miscellaneous therapies. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Thirty-one patients (41%) were treated with chemotherapy only, 15 (20%) were treated with chemotherapy 1 rituximab, 24 (32%) were treated with chemotherapy 1 radiotherapy, and 2 (3%) were treated with chemotherapy 1 rituximab 1 radiotherapy. One patient underwent observation alone after total resection, 1 received no therapy for 3 months for logistic reasons, and 1 patients remained without therapy.…”
Section: Resultsmentioning
confidence: 99%
“…EFS of 74% 6 5% for the entire cohort is comparable to that of children with CNS 1 systemic NHL and similar to the 2-year progression-free survival of 61% that was reported by the International PCNSL Collaborative Group in 29 2-to 21-year-old PCNSL patients. [11][12][13]15,16,23,29 Our favorable outcome has been achieved by histological subtype-directed polychemotherapy in most patients, suggesting that pediatric PCNSL can be successfully managed by protocols designed for children with CNS 1 systemic NHL, usually including high-dose methotrexate and high-dose cytarabine, steroids, and no irradiation (except for ALCL). [11][12][13]15,16,23,29 Our evaluation of prognostic factors found preexisting disorders to be associated with inferior EFS and OS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T‐cell receptor antigens are frequently not expressed and CD3 is more often detected in the cytoplasm than on the cell surface. With intensive frontline treatment, r/r disease occurs in 10–20% of patients (Landmann et al , ). NOTCH1 and FBXW7 mutations (Callens et al , ) and loss of heterozygosity at chromosome 6q (Bonn et al , ) were shown to be promising prognostic parameters of paediatric T‐LL.…”
Section: Lymphoblastic Lymphomamentioning
confidence: 99%